Monitoring Mitochondrial Function in Aedes albopictus C6/36 Cell Line during Dengue Virus Infection - María E. Santana-Román; Paola Maycotte; Salvador Uribe-Carvajal; Cristina Uribe-Alvarez; Nayeli Alvarado-Medina; Mohsin Khan; Aleem Siddiqui; Victoria Pando-Robles (Insects, 2021)
Aedes aegypti and Aedes albopictus mosquitoes are responsible for dengue virus (DENV) transmission in tropical and subtropical areas worldwide, where an estimated 3 billion people live at risk of DENV exposure. DENV-infected individuals show symptoms ranging from sub-clinical or mild to hemorrhagic fever. Infected mosquitoes do not show detectable signs of disease, even though the virus maintains a lifelong persistent infection. The interactions between viruses and host mitochondria are crucial for virus replication and pathogenicity. DENV infection in vertebrate cells modulates mitochondrial function and dynamics to facilitate viral proliferation. Here, we describe that DENV also regulates mitochondrial function and morphology in infected C6/36 mosquito cells (derived from Aedes albopictus). Our results showed that DENV infection increased ROS (reactive oxygen species) production, modulated mitochondrial transmembrane potential and induced changes in mitochondrial respiration. Furthermore, we offer the first evidence that DENV causes translocation of mitofusins to mitochondria in the C6/36 mosquito cell line. Another protein Drp-1 (Dynamin-related protein 1) did not localize to mitochondria in DENV-infected cells. This observation therefore ruled out the possibility that the abovementioned alterations in mitochondrial function are associated with mitochondrial fission. In summary, this report provides some key insights into the virus–mitochondria crosstalk in DENV infected mosquito cells.